2016
DOI: 10.1149/2.1121607jes
|View full text |Cite
|
Sign up to set email alerts
|

Electron Hopping of Tris (2,2-bipyridyl) Transition Metal Complexes M(bpy)2/33in Nafion

Abstract: Voltammetric currents of transition metal complexes in films on electrodes increase with electron self exchange (hopping) rate k11. In films, diffusion coefficients Df∝k11c*f, where k11 sets frequency of electron hopping attempts and c*f film concentration sets distance between probes. Cyclic voltammetry of Nafion films on electrodes for six probes, tris(2,2′-bipyridyl) complexes, M(bpy)z +3 where Mz + is Ru2+, Os2+, Fe2+, Cr3+, Co3+, and Co2+, demonstrates Df varies linearly with kH2O11, literature k11 measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…In this work, ion-selective membranes were doped not only with Co­(III) and Co­(II) complexes but also with the analogous complexes [Fe­(II)­(bipy) 3 ] 2+ , [Os­(II)­(bipy) 3 ] 2+ , and [Ru­(II)­(bipy) 3 ] 2+ . As reported in the literature, standard electron transfer rate constants for these three complexes are more than 5 orders of magnitude larger than for the corresponding cobalt complexes, which is consistent with fast electron transfer kinetics from these Fe­(II), Os­(II), and Ru­(II) complexes to gold electrodes underlying ion-selective membranes doped with these compounds.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In this work, ion-selective membranes were doped not only with Co­(III) and Co­(II) complexes but also with the analogous complexes [Fe­(II)­(bipy) 3 ] 2+ , [Os­(II)­(bipy) 3 ] 2+ , and [Ru­(II)­(bipy) 3 ] 2+ . As reported in the literature, standard electron transfer rate constants for these three complexes are more than 5 orders of magnitude larger than for the corresponding cobalt complexes, which is consistent with fast electron transfer kinetics from these Fe­(II), Os­(II), and Ru­(II) complexes to gold electrodes underlying ion-selective membranes doped with these compounds.…”
Section: Resultssupporting
confidence: 89%
“…Consequently, the CVs measured with 10 μm microelectrodes represent a convolution of both linear and spherical diffusion. The differences in E ° between the four complexes (see Table S1) agree within 0.05 V with values observed by Leddy and co-workers for Nafion films doped with the same type of complexes . Importantly, the small peak separation for experiments with [Co­(II)­(bipy) 3 ] 2+ , [Fe­(II)­(bipy) 3 ] 2+ , [Os­(II)­(bipy) 3 ] 2+ , and [Ru­(II)­(bipy) 3 ] 2+ confirms fast electron transfer kinetics in o -NPOE (see Table S1, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Early studies of electrode-supported redox polymers employed the cation-exchange material Nafion as a host matrix owing to its convenience and ability to strongly extract and electrostatically bind a wide range of redox-active cations. , Building on this foundation, the cell in Figure was initially tested on Nafion films containing exchanged MV 2+ ions. MV 2+ and its reduced radical cation (MV +• ) have rich vibrational spectra, and when excited near 660 nm, electrogenerated MV +• can be sensitively detected by resonance Raman scattering …”
Section: Results and Discussionmentioning
confidence: 99%
“…In progressing from 0.8 to −0.4 V (Figure , bottom), the upward bands reflect species whose composition within the confocal probe volume becomes greater at −0.4 V. The pair of peaks near 2090 cm –1 trace the formation of Fe(CN) 6 4– ions, while the strong peak near 1000 cm –1 and several weaker upward peaks toward higher frequency arise from the Sustainion matrix (Figure S4). The appearance of Sustainion bands in the difference spectrum can be attributed to the contraction of the polymer framework as chloride ions transfer from the film into the contacting electrolyte solution in response to the reduction of Fe(CN) 6 3– ions. , In the study of electrode-supported films prepared by entrapment of redox-active transition-metal compounds within inert ionomers, , it has been shown that small mobile ions derived from the electrolyte redistribute between the film and bulk solution to compensate for the charge imbalance that accompanies changes in the film oxidation state. , For Sustainion containing electrostatically bound Fe(CN) 6 3– ions, the reaction can be depicted as follows false( normalI normalm + false) n ( F e false( normalC normalN false) 6 3 ) + ( I m + ) normalC normall + normale .25em false( normalI normalm + false) false( n + 1 false) ( F e false( normalC normalN false) 6 4 ) + normalC normall false( normala normalq false) …”
Section: Results and Discussionmentioning
confidence: 99%